Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.12788/jhm.3249
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration, Not Calculation: A Qualitative Study of How Hospital Executives Value Hospital Medicine Groups

Abstract: receive financial support from hospitals. Determining a fair amount of financial support requires negotiation between HMG and hospital leaders. As the hospital medicine care model evolves, hospital leaders may regularly challenge HMGs to demonstrate the financial value of activities that do not directly generate revenue. OBJECTIVE: To describe current attitudes and beliefs of hospital executives regarding the value of contributions made by HMGs. DESIGN: Thematic content analysis of key informant interviews. PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…As a result, some healthcare administrators perceive their hospitalist programs as a financial loss and this perspective can impact the way they perceive their hospitalist program’s value proposition [ 24 ]. Despite this, in the US there is a general agreement that “hospitalists are here to stay” [ 17 , 18 ] and healthcare leaders need to focus instead on maximizing their partnership with hospitalist physicians in order to enhance care efficiency and quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, some healthcare administrators perceive their hospitalist programs as a financial loss and this perspective can impact the way they perceive their hospitalist program’s value proposition [ 24 ]. Despite this, in the US there is a general agreement that “hospitalists are here to stay” [ 17 , 18 ] and healthcare leaders need to focus instead on maximizing their partnership with hospitalist physicians in order to enhance care efficiency and quality.…”
Section: Discussionmentioning
confidence: 99%
“…A number of systematic reviews have suggested that hospitalist care is associated with reductions in length of stay (LOS) and cost of hospitalization along with improvements in patient satisfaction [ 15 , 16 ]. Similarly, studies in the United States (US) have shown widespread acceptance of the hospitalist model among hospital administrators [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, highlight hospitalists' nonfiscal contributions, especially in terms of crisis leadership, to continue engagement with executive leaders. 5 This may include a dialogue about the disproportionate influence of work relative value unit production on salary and about how to create compensation systems that can also recognize crisis readiness as an important feature of sustainability and quality care. The next pandemic surge may be weeks or months away, and hospitalists will again need to be leaders in the response.…”
Section: Navigating the Financial Challengesmentioning
confidence: 99%